(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This article presents the morphology and bioecology of the main pests of sweet pepper, spider mites, and greenhouse thrips. A chemical method of control against greenhouse thrips was used, in which Polo, 50% sus.c. (1.0 l/ha), Kapito, 50% em.c. (0.25 l/ha), and Desis, 2.5% em.c. (0.7 l/ha) were tested against the pest